Sedimentary facies of the prograding front of the Paraná River delta, Río de la Plata estuary, South America. (Latin American Journal of Sedimentology and Basin Analysis, 2021)
A sedimentological study of the prograding area of the Paraná River delta (PRD) is here presented with the aim of characterizing the deposits related to the last ~100 yr. of paleoenvironmental evolution and to contribute to facies models of bayhead deltas. Delta deposits are the result of the interaction of various processes and factors (principally hydrological characteristics, waves, tidal action, type and volume of sedimentary discharge, water depth, sea level, climate) that disperse the sediments transported to the river mouth (Wright, 1977). The Paraná River, together with the contribution of the Uruguay River, develops a bayhead delta into the Río de la Plata (RdP) estuary (Fig. 1a). The delta constitutes an extensive plain with a very low gradient, lined by numerous fluvial channels of diverse hierarchy, and a series of distributary mouth bars with a lobate morphology (Figs. 1c, 2). It is a fluvial-dominated delta, regulated by the hydrological regime of its drainage basin and modulated by the estuary dynamics (Iriondo, 2004; Cavallottoet al., 2005). This bayhead delta has a drainage area of 3.000.000 km2. The Paraná river supplies 160 million tons of sediment per year to the delta mouth, with ~145 million tons of suspended sediments (30% clays, 60-65% silts and 5-10% sands) and 15 million tons of sands as bottom load (Sarubbiet al., 2004). In the Uruguay River, the suspended load reaches 7 million tons per year of sediments, with a higher contribution of sandy bottom sediments (Urien, 1972). Several studies revealed a high-constructive dynamic for the Paraná river delta during the last decades, with progradation rates of 30 to 70 m per year since AD 1818 (Soldano, 1947; Codignotto and Marcomini, 1993; Pittauet al., 2007; Leal, 2011; Medina and Codignotto, 2013). In particular, the study area grew an average of 42-45 m per year between AD 1933-2016 (Marcominiet al., 2018; Fig. 3).             The PRD is placed at a temperate zone of southern South America, under a subhumid, mesothermal climate (periods 1981–1990 and 1991–2000; National Meteorological Service, 1992, 2003). Winds are mainly from the northeast and the southeast quadrants (Simionato and Vera, 2002), and are the main forcing of the RdP estuary circulation (Moreira et al., 2016). The estuary experiences a microtidal regime and the wave energy in the inner estuary is low (in average lower than 0.6 m high) and local (Moreira, 2016). Strong southeasterly wind (sudestada), that can last several days, triggers storm surges in the estuary and extensive floods in coastal areas (Seluchi, 1995). On the opposite, when ebb tides are accompanied by intense northeasterly winds, a very low water level happens (Simionatoet al., 2004). Fitogeographically, the PRD belongs to the Neotropical region, and the vegetation is strongly influenced by the landscape and the hydrologic regime (Kanduset al., 2006). At the subaerial deltaic plain, plant communities are characterized by riparian forest along the levees and graminoid type plants in the interior, while bulrush colonizes the proximal subaqueous delta (Fig. 4d).             Materials and methods include a geomorphologic-temporal evaluation, in-situ survey and sampling of surficial sediments and sediment cores in the lower subaerial and proximal subaqueous delta plains (34° 26'S, 58° 30' W; Fig. 3), accompanied by lab determinations and then facies analysis. Surficialsediments were sampled with a Snapper dredge and the sediment cores were extracted using 2.5 inches PVC tubes. Grain size was measured with a Malvern MastersizerHydro 2000 laser analyzer, after pretreatment to eliminate organic content by soaking samples in hydrogen peroxide solution (H2O2) and rinsed with distilled water. The textural results were statistically processed and evaluated following the Folk and Ward (1957) protocols (Table 1). Due to the common presence of heterolithic sediments and in order to obtain an improved interpretation of the relationship between grain size distribution and sedimentary processes, extreme member (EM) analysis (after Paterson and Heslop, 2015) was applied to identify subpopulations (parametric curve-fitting applying the Weibull distribution; Fig. 5). EM modelling of the studied deposits was guided by geologic criteria and examined in terms of sediment availability and transport-deposition processes, including particle trapping due to bulrush vegetation (a common process in the PRD). The textural characterization by means of ME results a convenient technique to interpret mixed sediments like the here studied. Particularly, it can be useful when the sediment sample are acquired with dredges or augers, methods that produce the loss of sedimentary structures but demand less time and logistics than to extract cores. Sediment cores were described in terms of grain-size, sedimentary structures, color (Munsell, 2000), biological remains, mass magnetic susceptibility (SM, using a Bartington MS2B sensor) and percentage of LOI550 and LOI950.             The time constrain for the core successions (ca. 1915-2017) was inferred by means of two main elements: correlation with a sediment core extracted about 15 km to the north of our study area and dated using radionuclide dating (210Pb and 137Cs) by (Schuerch et al., 2016) and the presence and depth of shells of Corbícula fluminea (Table 2), invader bivalve first recorded in the RdP estuary by ca. 1970 (Ituarte, 1981). The vertical growth rate of 1.52 cm per year (since year 1960) estimated for that core, that shows a comparable thickness and grain-size trend and represents a similar subaqueous delta subenvironment (Schuerch et al., 2016), was used in the here study sediment cores (Table 3). In a couple of studied cores there is some inconsistency between the two elements, possibly due to a higher rate of sedimentation. Besides, it is important to notice these estimations are relative age that have a degree of uncertainty due to these organisms not necessary may appear in all the sampled sites.             The inferred relationships of grain-size subpopulations and sediment transport-deposition, the analysis of the sediment cores (Figs. 6,7) and the evaluation of the geomorphological setting of surficial and core samples, allow proposing a series of lithofacies (Table 2) and facies associations (Table 4). Core location in a time series of aerial photograph and Google Earth® images (Fig. 3) and previous delta models and concepts (mainly those by Wright and Coleman, 1973; Coleman and Wright, 1975; Wright, 1977; Orton and Reading, 1993) were applied in the facies analysis. Principally, the theoretical model of friction-dominated effluents proposed by Wright (1977) can be applied to the PRD, developed in a shallow basin (inner estuary is less than 4 m deep; Urien, 1972; Fig. 2) that promotes turbulent bed friction.             The distributary mouth bars are laterally extensive (several km2), with very low slope (Fig. 4a-c) and crossed by shallow tidal channels. Bars are made up of massive or horizontal laminated beds forming heterolithic beds (sandy and muddy silt) and few fine-very fine sand and silty sand (bar crest) (Facies association F1, Table 4; Figs. 6, 7). This is interpreted as quick accumulation of tractive sediments, due to friction at the shallow river mouth, and then reworked by semidiurnal tidal currents and exceptional storm surges and accompanied by settling of fines from suspension. Once these shoals are stabilized by bulrushvegetation the sedimentation is dominated by suspension and particle trapping by vegetation (Fig. 4d), with eventual very low currents. Finally,the bar becomes an island of the lower subaerial delta plain, dominated by accumulation from flooding events. During this final stage clayey silt and silty clay, with the largest values of LOI550 of all core sediments, are deposited by flooding from the distributary channels (Facies association F5). Facies association F2 represents high energy deposition of sand and silty sand, usually with shells, due to exceptional storm surges or fluvial flooding. Deposits of interdistributary bays (Fig. 4e), included in facies association F4, are dominated by horizontal and heterolithic laminated, clayed silt with low LOI550 (Figs. 6,7). Deposits of subaqueous distributary channel (Fig. 4f) are fine-very fine sand and silty sand interlayered with silt and muddy silts with heterolithic laminations (Facies association F3a, Figs. 6,7). In core D11-T2 a succession with interbedded fine-very fine sand and sandy silt-silt with inclined heterolithic stratification (HIS) was identified (Facies association F3b, Fig. 7), and interpreted as subaqueous channel deposits, developed next to distributary bars (Fig. 3e).             The textural characterization by means of ME proves to be a convenient technique to interpret mixed sediments like the here studied. Particularly, it can be useful when the sediment sample are acquired with dredges or augers, methods that produce the loss of sedimentary structures but demand less time and logistics than to extract cores. The proposed lithofacies and facies association will allow to systematize the sedimentological studies of the DRP and research of prograding deposits of bayhead deltas fed by big rivers with a sandy silt load.